2018
DOI: 10.3389/fphys.2018.00281
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of a Dual Domain Carbonic Anhydrase From the Ctenidium of the Giant Clam, Tridacna squamosa, and Its Expression Levels After Light Exposure, Cellular Localization, and Possible Role in the Uptake of Exogenous Inorganic Carbon

Abstract: A Dual-Domain Carbonic Anhydrase (DDCA) had been sequenced and characterized from the ctenidia (gills) of the giant clam, Tridacna squamosa, which lives in symbiosis with zooxanthellae. DDCA was expressed predominantly in the ctenidium. The complete cDNA coding sequence of DDCA from T. squamosa comprised 1,803 bp, encoding a protein of 601 amino acids and 66.7 kDa. The deduced DDCA sequence contained two distinct α-CA domains, each with a specific catalytic site. It had a high sequence similarity with tgCA fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 69 publications
(109 reference statements)
0
16
0
Order By: Relevance
“…Our results indicate that SGLT1-like was regulated principally through translation, as light exposure did not have a significant effect on its transcript level. This differs from Dual Domain Carbonic Anhydrase (Koh et al, 2018), Glutamine Synthetase (Hiong et al, 2017a) and Na + /H + Exchanger 3-like (Hiong et al, 2017b), of which both the transcript level and the protein abundance increase significantly in the ctenidium of T. squamosa during 12 h of light exposure. Overall, these results corroborate the proposition that T. squamosa could perform lightenhanced glucose/urea absorption.…”
Section: Discussion Sglt1-like From T Squamosa: Molecular Characterimentioning
confidence: 63%
See 3 more Smart Citations
“…Our results indicate that SGLT1-like was regulated principally through translation, as light exposure did not have a significant effect on its transcript level. This differs from Dual Domain Carbonic Anhydrase (Koh et al, 2018), Glutamine Synthetase (Hiong et al, 2017a) and Na + /H + Exchanger 3-like (Hiong et al, 2017b), of which both the transcript level and the protein abundance increase significantly in the ctenidium of T. squamosa during 12 h of light exposure. Overall, these results corroborate the proposition that T. squamosa could perform lightenhanced glucose/urea absorption.…”
Section: Discussion Sglt1-like From T Squamosa: Molecular Characterimentioning
confidence: 63%
“…The surface area is further increased by numerous water channels found below the filaments inside the ctenidium. The ctenidium of T. squamosa is known to express transporters and enzymes (Ip et al, 2015) related to nitrogen transport and assimilation (DUR3-like, Chan et al, 2018;Ammonia Transporter 1, Boo et al, 2018;Glutamine Synthetase, Hiong et al, 2017a), inorganic carbon absorption (Dual Domain Carbonic Anhydrase; Koh et al, 2018) and proton excretion (Na + /H + Exchanger 3-like, Hiong et al, 2017b; Vacuolar-type H + -ATPase subunit A, Ip et al, 2018). In the present study, we demonstrated that SGLT1-like was expressed predominantly in the ctenidium of T. squamosa.…”
Section: Discussion Sglt1-like From T Squamosa: Molecular Characterimentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, these proteins have also been associated with biomineralization (Medakovic et al 2000 ; Zhang et al 2012 ). Specifically, a suite of novel molecular studies lend support to the role of these carbonic anhydrases in acquisition of inorganic carbon during calcification (Wang et al 2017 ; Koh et al 2018 ; Chew et al 2019 ). Additionally, it has been suggested that NHE proteins promote calcification by aiding in the removal of proton byproducts (Hiong et al 2017 ; Cao-Pham et al 2019 ).…”
Section: Discussionmentioning
confidence: 99%